Statistical Evaluation of Methods for Determining Asphalt Content and Aggregate Gradation in Asphalt Mixtures - Castro Fernández, Pedro (2025)
The purpose of this study is to assess the accuracy and precision of various laboratory techniques used to determine the asphalt content and aggregate gradation in asphalt concrete mixtures.